Effect of Polyherbal Formulated Teaonsperm Count, Motility and Viability in Wistar Rats - Uwaya, Dickson Onyenmulo; Udemmadu, Christian Chukwuebuka; Olayinka, Juilet N. (Darul Yasin Al Sys, 2026)
Polyherbal formulations have attracted increasing scientific interest because their combined constituents may produce synergistic therapeutic effects. This study evaluated the effects of an aqueous polyherbal tea extract on sperm count, motility, viability, and testicular oxidative stress markers in male Wistar rats. Twenty rats were randomly allocated into five groups of four animals: a distilled-water control group, a carbamazepine-treated group receiving 20 mg/kg, a sildenafil citrate-treated group receiving 5 mg/kg, and two treatment groups receiving 5 or 10 mg/kg of the polyherbal tea extract orally for 21 days. Following treatment, the animals were sacrificed by cervical dislocation, and sperm count, progressive and non-progressive motility, and viability were assessed. Testicular tissue homogenates were also analysed for superoxide dismutase, catalase, glutathione, and malondialdehyde. The polyherbal tea produced no significant change in sperm count compared with the distilled-water and carbamazepine groups (p > .05). However, the extract significantly increased progressive sperm motility and sperm viability while reducing immotile sperm, non-progressive motility, and non-viable sperm (p < .05 or p < .01). Superoxide dismutase and catalase activities were significantly elevated following treatment with the polyherbal tea compared with the distilled-water and carbamazepine groups (p < .05). The extract and sildenafil citrate also significantly reduced malondialdehyde levels (p < .05), whereas glutathione levels remained unchanged across the treatment groups (p > .05). These findings demonstrate that the aqueous polyherbal tea extract improves sperm motility and viability without affecting sperm count, potentially through enhanced testicular antioxidant activity and reduced lipid peroxidation. The study provides preliminary evidence supporting further investigation of the formulation as a potential intervention for improving male reproductive function.